Therapeutic apheresis using a mononuclear cell program to lower the microfilaria burden of a 23‐year‐old African woman with loiasis. Issue 3 (15th June 2016) - Zhao, Yong; Alexander, Brian; Bailey, Jeffrey A.; Welch, Linda; Greene, Mindy; Vauthrin, Michelle; Mitchell, Michael; Weinstein, Robert
Abstract : Apheresis has been used to lower the parasite burden of patients with Loa loa infection, but there are no reports regarding how to do this using modern, continuous flow equipment with a currently available program. A 23‐year‐old female refugee from Cameroon with known Loa loa infection presented to our Emergency Department with acute mental status changes and a picture of encephalitis. Lumbar puncture revealed Loa loa in her cerebrospinal fluid. Her midday blood microfilaria count was 15, 000/mL. Because treatment with diethylcarbamazine was under consideration, we were asked to lower her parasite burden using apheresis. One single 2‐total blood volume apheresis using the mononuclear cell program (without hydroxyethyl starch) on a COBE ® Spectra Apheresis System decreased the microfilarial load from 15, 000/mL to 10, 666/mL, a 29% reduction. J. Clin. Apheresis 32:200–202, 2017. © 2016 Wiley Periodicals, Inc.